Infective endocarditis caused by Neisseria mucosa on a prosthetic pulmonary valve with false positive serology for Coxiella burnetii – The first described case. (2021) - Altdorfer, Antoine; Pirotte, Benoit F.; Gaspard, Laura; Gregoire, Emilien; Firre, Eric; Moerman, Filip; Moonen, Martial; Sanoussi, Ahmed; Van Esbroeck, Marjan; Mori, Marcella
Abstract: We present a case of infective endocarditis (IE) on a prosthetic pulmonary valve in a 36-year-old patient with tetralogy of Fallot (TOF). The patient underwent valve replacement surgery and active antibiotic treatment against Gram-negative cocci (Piperacillin Tazobactam then Ceftriaxone) for a total duration of 42 days with a favourable outcome. The causative agent was Neisseria mucosa which was identified on the infected valve by sequencing of 16S ribosomal RNA. To our knowledge, this is the first described case of a N. mucosa infective endocarditis on a pulmonary valve. Initially, serologies performed in clinical settings by immunofluorescence for Coxiella burnetii antibodies showed a major increase in phase I IgG titers at 1024 (normal values <16) corresponding with the diagnostic criteria for Q fever endocarditis. However, this diagnosis could not be confirmed by the National Reference Center, making it the first reported case of a false positive serology for C. burnetii during an infection due to Neisseria spp.